Lasting effects of cancer and its treatment on employment and finances in adolescent and young adult cancer survivors. Issue 11 (1st February 2019) - Ketterl, Tyler G.; Syrjala, Karen L.; Casillas, Jacqueline; Jacobs, Linda A.; Palmer, Steven C.; McCabe, Mary S.; Ganz, Patricia A.; Overholser, Linda; Partridge, Ann; Rajotte, Emily Jo; Rosenberg, Abby R.; Risendal, Betsy; et al.
Abstract : Background: The impact of cancer and its treatment on employment and financial burden in adolescents/young adults (AYAs) is not fully known. Methods: Eligibility for this cross‐sectional study of AYA cancer survivors included the diagnosis of a malignancy between ages 18 and 39 years and survey completion within 1 to 5 years from diagnosis and ≥1 year after therapy completion. Participants were selected randomly from the tumor registries of 7 participating sites and completed an online patient‐reported outcomes survey to assess employment and financial concerns. Treatment data were abstracted from medical records. Data were analyzed across diagnoses and by tumor site using logistic regression and Wald‐based 95% confidence intervals adjusting for age (categorized), sex, insurance status, education (categorized), and treatment exposures. Results: Participants included 872 survivors (breast cancer, n = 241; thyroid cancer, n = 126; leukemia/lymphoma, n = 163; other malignancies, n = 342). Exposure to chemotherapy in breast cancer survivors was associated with an increase in self‐reported mental impairment in work tasks (odds ratio [OR], 2.66) and taking unpaid time off (OR, 2.62); survivors of "other" malignancies reported an increase in mental impairment of work tasks (OR, 3.67) and borrowing >10, 000 (OR, 3.43). Radiation exposure was associated with an increase of mental impairment in work tasks (OR, 2.05) in breast cancer survivors, taking extended paid time off work in thyroid cancer survivors (OR, 5.05), and physical impairment in work tasks in survivors of "other" malignancies (OR, 3.11). Finally, in survivors of "other" malignancies, having undergone surgery was associated with an increase in physical (OR, 3.11) and mental impairment (OR, 2.31) of work tasks. Conclusions: Cancer treatment has a significant impact on AYA survivors' physical and mental work capacity and time off from work. Abstract : In a multicenter, cross‐sectional study of adolescent and young adult cancer survivors between ages 18 and 39 years, from 1 to 5 years after diagnosis, and greater than 1 year after therapy completion, the associations of treatment‐related factors with the likelihood of physical and mental impairment of work tasks as well as the likelihood of changes in employment, including any time off from work, are evaluated. Findings reveal that cancer treatment has significant financial and employment implications as well as a significant impact on adolescent and young adult survivors' physical and mental work capacity.